Respuesta :
Answer:
[tex]y = (x-6) ^ 2 -16[/tex]
Step-by-step explanation:
The vertex form for a quadratic equation has the following form:
[tex]y = (x-h) ^ 2 + k[/tex]
Where the vertice of the equation is the point (h, k)
To transform the equation [tex]y = x ^ 2 -12x +20[/tex] in its vertex forms we must find its vertex.
Be a quadratic equation of the form:
[tex]ax ^ 2 + bx + c[/tex]
Where a, b and c are real numbers, then the vertex of the equation will be:
[tex]x = - \frac{b}{2a}[/tex]
For the given equation:
[tex]b = -12\\a = 1[/tex]
Therefore the vertice is:
[tex]x = - \frac{-12}{2(1)}\\\\x = 6[/tex]
Now we substitute x = 6 into the equation and find the value of k.
[tex]y = (6) ^ 2 -12 (6) +20\\\\y = -16 = k[/tex]
Therefore the vertice is: (6, -16)
And the equation is:
[tex]y = (x-6) ^ 2 -16[/tex]
Answer:
y = (x-6)²-16
Step-by-step explanation:
We have given a quadratic equation.
y = x²-12x+20
We have to rewrite above equation in vertex form.
y = a(x-h)²+k is vertex form of quadratic equation.
Adding and subtracting (-6)² to both sides of above equation, we have
y = x²-12x+20+(-6)²-(-6)²
y = x²-12x+(-6)²+20-(-6)²
y = (x-6)²+20-36
y = (x-6)²-16
The vertex form is y = (x-6)²-16 where (6,16) is vertex for equation of parabola.